LbNrt RNA silencing in the mycorrhizal symbiont L accaria bicolor reveals a nitrate-independent regulatory role for a eukaryotic NRT2-type nitrate transporter - Kemppainen, Minna Johanna (2013)
Fungal nitrogen metabolism plays a fundamental role in function of mycorrhizal symbiosis and consequently in nutrient cycling of terrestrial ecosystems. Despite its global ecological relevance the information on control and molecular regulation of nitrogen utilization in mycorrhizal fungi is very limited. We have extended the nitrate utilization RNA silencing studies of the model mycorrhizal basidiomycete, Laccaria bicolor, by altering the expression of LbNrt, the sole nitrate transporter-encoding gene of the fungus. Here we report the first nutrient transporter mutants for mycorrhizal fungi. Silencing of LbNrt results in fungal strains with minimal detectable LbNrt transcript levels, significantly reduced growth capacity on nitrate and altered symbiotic interaction with poplar. Transporter silencing also creates marked co-downregulation of whole Laccaria fHANT-AC (fungal high-affinity nitrate assimilation cluster). Most importantly, this effect on the nitrate utilization pathway appears independent of extracellular nitrate or nitrogen status of the fungus. Our results indicate a novel and central nitrate uptake-independent regulatory role for a eukaryotic nitrate transporter. The possible cellular mechanisms behind this regulation mode are discussed in the light of current knowledge on NRT2-type nitrate transporters in different eukaryotes.